Review of the Volume “Organizational Culture and Educational Management”, authored by Daniel Terec-Vlad, Michaela Fomin, Oana Miruna Oprea and Loredana Terec-Vlad - Ursăciuc, Aurelia (Theleologicae International Journal of Postmodern Studies, 2022)
The book Organizational Culture and Educational Management, published in 2021 by Etica Pro Expert Publishing House, provides a detailed analysis of the dynamics of contemporary organizations, with a particular focus on educational systems. Structured into eight chapters, the volume explores fundamental concepts such as organizational culture, communication, professional ethics, and academic integrity. Moreover, the authors address the challenges brought by the COVID-19 pandemic, emphasizing the lessons learned and the necessary directions for transformation in educational management. Through an interdisciplinary and practice-oriented approach, the book combines theoretical foundations with concrete examples, offering applicable solutions for the development of organizations and the improvement of the quality of educational processes.